Data on inelastic processes in low-energy collisions of barium atoms and ions with hydrogen atoms and anions. Issue 3 (23rd June 2018) - Belyaev, Andrey K; Yakovleva, Svetlana A
ABSTRACT: Inelastic rate coefficients for 686 partial processes in low-energy Ba + H, Ba + + H −, Ba + + H and Ba 2+ + H − collisions are calculated. These data are needed for the non-local thermodynamic equilibrium (non-LTE) modelling of Ba i and Ba ii spectra, especially in cool stellar atmospheres. The calculations of the rate coefficients are performed by means of the quantum model approach, based on the asymptotic semi-empirical method for the electronic structure calculations and on multichannel formulas for the non-adiabatic nuclear dynamical calculations. The inelastic rate coefficients for all transitions between the 17 lowest covalent states and one ionic molecular state in Ba + H and Ba + + H − collisions, as well as the inelastic rate coefficients for all transitions between the 19 lowest covalent states and one ionic molecular state in Ba + + H and Ba 2+ + H − collisions are calculated. In Ba + + H − collisions, the highest rate coefficients correspond to the mutual neutralization processes into the Ba(6s6p 1 P°), Ba(6s7s 3 S) and Ba(6s7s 1 S) final states, with the largest value of 5.93 × 10 − 8 cm 3 s −1 at T = 6000 K for the process Ba + + H − → Ba(6s7s 3 S) + H. The highest rate coefficient for excitation and de-excitation processes in Ba + H collisions corresponds to the Ba(6s7s 1 S) → Ba(6s7s 3 S) transition, with the value of 7.62 × 10 − 9 cm 3 s −1 at T = 6000 K. In Ba 2+ + H − collisions, the highest rate coefficients correspond to the neutralization processes into the Ba + ( 7p 2 P°), Ba + ( 4f 2 F°), Ba + ( 6d 2 D) and Ba + ( 7s 2 S) final states. The highest neutralization rate has the value of 3.96 × 10 − 8 cm 3 s −1 at T = 6000 K for the Ba 2+ + H − → Ba + ( 7p 2 P°) + H process. The largest rate coefficient for excitation and de-excitation processes in Ba + + H collisions corresponds to the Ba + (7 s 2 S ) → Ba + ( 6p 2 P°) transition, with the value of 1.23 × 10 −9 cm 3 s −1 at T = 6000 K.